Two-pion Bose-Einstein correlations in pp collisions at √s=900 GeV - Aamodt, Kenneth; Angelov, Venelin; Busch, Oliver; Glässel, Peter; Grajcarek, Robert; Herrmann, Norbert; Klein, Jochen; Mercado Pérez, Jorge; Oyama, Ken; Pachmayer, Yvonne C.; Schicker, Rainer; Schweda, Kai; et al. (Physical review. D, Particles, fields, gravitation, and cosmology, 2010)
We report on the measurement of two-pion correlation functions from pp collisions at √s=900 GeV performed by the ALICE experiment at the Large Hadron Collider. Our analysis shows an increase of the Hanbury Brown-Twiss radius with increasing event multiplicity, in line with other measurements done in particle- and nuclear collisions. Conversely, the strong decrease of the radius with increasing transverse momentum, as observed at the Relativistic Heavy Ion Collider and at Tevatron, is not manifest in our data.
*ALICE Collaboration: K. Aamodt, V. Angelov, O. Busch, P. Glässel, R. Grajcarek, N. Herrmann, J. Klein, J. Mercado Pérez, K. Oyama, Y. Pachmayer, R. Schicker, K. Schweda, H.K. Soltveit, J. Stachel, S. Vallero, B. Windelband [und 1046 weitere Personen]
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Gesehen am 14.11.2022